The Impact of Direct and Indirect Feedback on Idiom Translating Skill of Iranian EFL College Students - Vahid Edalati Bazzaz; Maryam Niami; Shahrbanoo Mohammadi (Center of Language and Cultural Studies [CLCS], 2019)
This study examines the effectiveness and efficacy of teachers' direct vs. indirect feedback on students' idiom translating skills. To achieve this purpose, 23 Iranian university students from two intact classes were randomly assigned to two experimental groups: direct feedback group in which the teacher located and gave the correct translation of idiom and indirect feedback group in which the teacher only noted the number of wrong translations of idioms. The study lasted 10 weeks in the course of which the participants had to translate a short text from â€œIdioms and Metaphorical Expressions in Translationâ€ by â€œGhaffar Tajalliâ€. The study included a pre-test, a treatment for experimental groups, and a post-test to see whether or not the treatment had been effective. The statistical analyses indicated the effectiveness of direct feedback inaccurate use of the translation of idioms. Therefore, the results can provide some useful insights into translating courses, syllabus design, and translator training courses.